2017
DOI: 10.1186/s12944-017-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipids bearing extruded-spheronized pellets for extended release of poorly soluble antiemetic agent—Meclizine HCl

Abstract: BackgroundAntiemetic agent Meclizine HCl, widely prescribed in vertigo, is available only in immediate release dosage forms. The approved therapeutic dose and shorter elimination half-life make Meclizine HCl a potential candidate to be formulated in extended release dosage form. This study was aimed to develop extended release Meclizine HCl pellets by extrusion spheronization using natural and synthetic lipids. Influence of lipid type, drug/lipid ratio and combinations of different lipids on drug release and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The sphericity of pellets also became poor and irregular with CW [ 58 ]. Faaiza et al reported that the CW is the best release retarding agent for poorly soluble drug- Meclizine HCl due to the absence of pores but destruct the morphology of pellets [ 59 ]. While, previously reported studies showed that the release of theophylline was retarded up to 3 h only and showed burst release was found even when CW was used in higher concentrations [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sphericity of pellets also became poor and irregular with CW [ 58 ]. Faaiza et al reported that the CW is the best release retarding agent for poorly soluble drug- Meclizine HCl due to the absence of pores but destruct the morphology of pellets [ 59 ]. While, previously reported studies showed that the release of theophylline was retarded up to 3 h only and showed burst release was found even when CW was used in higher concentrations [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only some additional peaks were observed before the spectra of Atenolol, might be associated with the different composition of CW. A researcher has also reported extra peaks of aluminum, copper, and zinc, in CW spectrum, due to its vegetable origin [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flow properties of both immediate and coated pellets were determined by evaluating bulk density, tapped density, compressibility index, Hausner ratio, and angle of repose "α". These parameters were calculated using the following equations (1) where M is the mass of pellets, V o and V f are the bulk and tapped volumes of pellets respectively. Compressibility index 11-15 and Hausner ratio 1.12-1.18 show good flow properties, whereas, compressibility index ≤ 10 and Hausner ratio 1.00-1.11 exhibit excellent flow properties.…”
Section: Drug Excipient Compatibilitymentioning
confidence: 99%
“…It is a non-destructive technique in which pellets and their cross-sections were bombarded with an electron beam, resulting in the emission of X-rays that are specific to each element. These emitted X-rays were detected by X-ray spectrometer 1 .…”
Section: Drug Excipient Compatibilitymentioning
confidence: 99%
See 1 more Smart Citation